Pisum sativum L. ‘Eso’: Metabolic Profiling of Yellow Seeds to Define the Optimal Harvest Time - Adriano Patriarca; Fabio Sciubba; Alberta Tomassini; Ottavia Giampaoli; Michele De Rosa; Federico Marini; Walter Aureli; Alfredo Miccheli; Elisa Brasili (Agriculture, 2024)
The yellow pea (Pisum sativum L. ‘Eso’, sin. Lathyrus oleracaeus Lam.(YP)) is an annual herbaceous plant that belongs to the Fabaceae family. Peas, along with other legumes, are an excellent source of proteins and essential amino acids; the yellow variety is known for maintaining a good protein profile even if subjected to industrial processing. However, the presence of antinutrients, such as phytates and oligosaccharides, limits its consumption as a fresh legume to its use as a source of isolated proteins or for animal feed. The aim of the study is to evaluate the changes in the entire phytochemical profile of YP seeds as a function of the harvest time. YPs harvested at about 40, 50, 60, and 70 days from sowing were examined by high-resolution NMR spectroscopy employing 1H-NMR, 1H-1H TOCSY, and 1H-13C HSQC. In total, 40 molecular species were identified and quantified; it was observed that there was a monotonous decrease in amino acids, carbohydrates, and secondary metabolites as a function of time. Antinutrient levels increased, but only in later sampling times. This study identified the optimal harvest time for yellow peas “Eso” in the fortieth day from sowing, adding new information about the best nutritional outcome for humans.